Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater